An overview of drugs for the treatment of Mycobacterium kansasii pulmonary disease. (March 2022) - Srivastava, Shashikant; Pasipanodya, Jotam G.; Heysell, Scott K.; Boorgula, Gunavanthi D.; Gumbo, Tawanda; McShane, Pamela J.; Philley, Julie V.
Highlights: Repurposing drugs for treatment of Mycobacterium kansasii pulmonary disease. We report 18 drugs showing efficacy against M. kansasii . 10 of 18 drugs showed better kill compared with drugs used in standard therapy. Preclinical PK/PD studies are warranted to test these drugs in combination. There is an opportunity to develop shorter-duration regimens for M. kansasii . ABSTRACT: Objectives: The aim of this study was to determine and compare the efficacy of drugs to treat Mycobacterium kansasii ( Mkn ) pulmonary disease by performing minimum inhibitory concentration (MIC) determination and time–kill studies. Methods: We determined the MICs to 13 drugs against the Mkn standard laboratory strain ATCC 12478 and 20 clinical isolates and performed time–kill studies with 18 drugs from different classes using the standard laboratory strain of Mkn . The β-lactam antibiotics were tested with or without the combination of the β-lactamase inhibitor avibactam. An inhibitory sigmoid Emax model was used to describe the relationship between drug concentrations and bacterial burden. Results: Among the 13 tested drugs in the MIC experiments, the lowest MIC was recorded for bedaquiline. Among the 18 drugs used in the time–kill studies, maximum kill with cefdinir, tebipenem, clarithromycin, azithromycin, moxifloxacin, levofloxacin, tedizolid, bedaquiline, pretomanid and telacebac was greater than that for some of the drugs (isoniazid, rifampicin and ethambutol) used in standard combination therapy. Conclusion: We report preclinical data on the efficacy and potency of drugs that can potentially be repurposed to create a safe, effective and likely shorter-duration regimen for the treatment of Mkn pulmonary disease.